Latin American Science Fiction
IX, 241 p. 12 illus.
Keywords: Combining work by critics from Latin America, the USA, and Europe, Latin American Science Fiction: Theory and Practice is the first anthology of articles in English to examine science fiction in all of Latin America, from Mexico and the Caribbean to Brazil and the Southern Cone. Using a variety of sophisticated theoretical approaches, the book explores not merely the development of a science fiction tradition in the region, but more importantly, the intricate ways in which this tradition has engaged with the most important cultural and literary debates of recent year.